Modeling of the two shuttle box system within the internal logistics system using simulation software - Strnad David (De Gruyter, 2021)
The efficiency and effectiveness of the production system are influenced by the logistical arrangement of material flows. The smooth production, especially for assembly lines in the required quantity and at the required time (JIT or JIS systems), is currently ensured by automatically controlled towing sets (logistics trains), which consist of a tractor and several trucks. Another factor that affects the smooth production of assembly lines is the system of controlling the circulation of transport units. The number of transport units used in combination with the transport system significantly affects the efficiency of assembly workplaces. This article presents an analysis of the supply of assembly workplaces using a system of two shuttle boxes. The aim of this article is to investigate the influence of transport speed and capacity on the smoothness of the assembly process. Within the described analysis, the transport of 50,000 components is analyzed using a simulation model, while the length of the transport route is 32 km and 65 transport units per shift are used.